Qualitative Development of the PROMIS(®) Pediatric Stress Response Item Banks - Bevans, Katherine B. (Oxford University Press, 2013)
Objective To describe the qualitative development of the Patient-Reported Outcome Measurement Information System (PROMIS®) Pediatric Stress Response item banks. Methods Stress response concepts were specified through a literature review and interviews with content experts, children, and parents. A library comprising 2,677 items derived from 71 instruments was developed. Items were classified into conceptual categories; new items were written and redundant items were removed. Items were then revised based on cognitive interviews (n = 39 children), readability analyses, and translatability reviews. Results 2 pediatric Stress Response sub-domains were identified: somatic experiences (43 items) and psychological experiences (64 items). Final item pools cover the full range of children’s stress experiences. Items are comprehensible among children aged ≥8 years and ready for translation. Conclusions Child- and parent-report versions of the item banks assess children’s somatic and psychological states when demands tax their adaptive capabilities.